Find the general solution of the following.
Attachments:
![](https://hi-static.z-dn.net/files/dad/b66acc7ab1726d9ccbb7246236387982.jpg)
Answers
Answered by
2
cos(x+π/10) = 0
Therefore,
x + π/10 = (2n+1)π/2
Therefore,
General solution for x is
x = (2n+1)π/2 - π/10
Hope this helps you !
Therefore,
x + π/10 = (2n+1)π/2
Therefore,
General solution for x is
x = (2n+1)π/2 - π/10
Hope this helps you !
Answered by
0
Answer:
|
y
|
=
e
x
−
x
+
c
Explanation:
y
'
=
y
e
x
−
y
⇒
d
y
d
x
=
y
(
e
x
−
1
)
separate variables
∫
d
y
y
=
∫
(
e
x
−
1
)
d
x
ln
|
y
|
=
e
x
−
x
+
c
Similar questions